Fake democracies and the political consequences of the Christian notion of person - Forcades i Vila, Teresa (Resistance and visions, 2014)
'Fake democracies' are systems of governance that allow their citizens to vote, but then lack effective controls to avoid that those elected legislate and rule against the interests or even against the explicit will of the majority. This is a complex phenomenon present in western capitalist societies at the turn of the 21st century that needs to be studied carefully. In this article, I analyze the theological notions of co-creation, unity in diversity, inseparability of love and freedom, and metanoia, in order to emphasize their potential for grounding a notion of person able to carry on the political changes needed to transform fake democracies into true ones. To the notion of 'co-creation' corresponds a subject (a person) able to assume political responsibility at the individual and at the collective level. To the notion of 'unity in diversity' corresponds a subject (a person) able to foster plurality and queer identities. To the notion of “inseparability of love and freedom” corresponds a subject (a person) able to overcome gender stereotypes and false individualistic freedom. And finally, to the notion of metanoia corresponds a subject (a person) able to understand and to carry on a permanent revolution. This can be a Christian theological contribution to a necessary and urgent social change. A theological contribution inspired in the gospel that, far from being exclusivist, understands itself as being in dialogue with all other currents of thought that feel as their own the pleas for justice of the poor.